Issues of maltreatment in high performance athlete development: Mental toughness as a threat to athlete welfare - Kerr, G.; Stirling, A. (Routledge handbook of talent identification and development in sport, 2017)
For centuries, people have been fascinated with highly talented people and the means by which they actualize their potential. In this chapter, the topic of talent development in sport is briefly introduced with a focus on `mental toughness` as a perceived requirement for athletic success. The topic of mental toughness and its relationship to high performance sport talent development is reviewed, critiqued, and proposed as a guise for athlete maltreatment with potentially harmful effects on athletes. This chapter concludes with recommendations for talent development strategies that are more consistent with healthy psychosocial development and learner-centred educational practices to advance both personal and performance success of high performance athletes.